How relevant are personas in open-source software development? - Chelly, Ahmed; Hamza, Salma; Khan, Javed Ali (Frontiers in Computer Science, 2025)
IntroductionOpen-source software (OSS) projects, characterized by distributed development and volunteer contributions, face challenges in prioritizing user-centered design and usability. This difficulty arises because these projects are primarily driven by developers who focus on technical contributions. As a result, usability and user experience (UX) considerations are often neglected, leading to software that may not meet the needs of its broad and diverse users.MethodsTo address this issue, we explore the potential of using user personas which are fictional characters representing real user groups, to enhance user-centered design in OSS projects. Personas promote empathy and a deeper understanding of user needs, thereby improving alignment between developers and users. We conducted an experimental study on three OSS projects: Moodle, Lichess, and Audacity. Personas were created for each project and refined based on feedback from industry experts.ResultsDevelopers rated personas highly for credibility (86%), consistency (79%), and friendliness (86%), highlighting their relevance in OSS projects. A follow-up experiment with students confirmed these findings, with consistency (79%) demonstrating personas' role in improving usability and aligning developers with user needs.DiscussionWhile adoption remains limited due to technical priorities (only 14% of developers and 34% of students found personas useful and expressed willingness to adopt them), personas show significant potential to enhance user-centered design in OSS. Further research is needed to understand developers' reluctance to adopt this technique and explore strategies to integrate personas more effectively into OSS workflows. This study's novelty lies in its empirical exploration of personas within OSS, providing quantitative evidence of their effectiveness in improving usability and user-centered design.